Secular change in morphological cranial and mandibular trait frequencies in European Americans born 1824–1987. Issue 3 (15th August 2020) - Kilroy, Grace S.; Tallman, Sean D.; DiGangi, Elizabeth A.
Abstract: Objectives: Secular change in cranial and postcranial morphometrics and morphological traits has been documented in several studies. However, to date, few studies have addressed temporal changes occurring in the expression of cranial morphological traits commonly used in ancestry estimation. This study examines secular change in the expression of 23 cranial and mandibular morphological traits; accounting for age‐at‐death, sex, and year‐of‐birth. Materials & Methods: Data were collected on 23 morphological cranial and mandibular traits for European American individuals (19–97 years of age) from the Hamann‐Todd Skeletal Collection ( n = 518) and the William M. Bass Donated Skeletal Collection ( n = 602). Individuals were divided into six birth‐year cohorts: 1824–1849 (Cohort 1), 1850–1874 (Cohort 2), 1875–1899 (Cohort 3), 1900–1924 (Cohort 4), 1925–1949 (Cohort 5), and 1950–1987 (Cohort 6). Results: Statistical analyses, including Pearson's chi‐square, correspondence analysis, and ordinal regression, demonstrate that secular changes have occurred in 11 traits, including: anterior nasal spine (ANS); malar tubercle (MT); nasal bone contour (NBC); postbregmatic depression (PBD); supranasal suture (SPS); transverse palatine suture (TPS); zygomaticomaxillary suture (ZS); ascending ramus shape (ARS); gonial angle flare (GAF); mandibular tori (MDT); and posterior ramus edge inversion (PREI), with changes occurring in both sexes for ANS, MT, TPS, ZS, GAF, MDT, and PREI. Significant changes in trait expression were found predominately between Cohorts 3 and 4, and Cohorts 4 and 5. While the sex of an individual affected the expression of ANS, MT, NBC, PBD, SPS, ZS, ARS, GAF, and PREI, age‐at‐death only affected MT and PREI. Discussion: This study demonstrates that secular change in morphological cranial and mandibular traits has occurred over the last two centuries in European Americans, with the most considerable change appearing at the turn of the twentieth century. Changes in morphological trait expression over a relatively short period of time correspond with changes seen in craniometric analyses and correlate with the industrialization of society and environmental and cultural changes, such as medical advancements, nutrition, and population health/stress.